Yes, you can and yes, it is.
Considering, for example, the non-negative case, we have a more general property:
$$O(f)\cdot O(g) = O(f\cdot g )$$
Let's take $ \varphi \in O(f) \cdot O(g) $. Then we have $\varphi = \varphi_{1} \cdot \varphi_{2}$ where
$$\exists C_{1} > 0, \exists N_{1} \in \mathbb{N}, \forall n > N_{1},\ \varphi_{1} \leqslant C_{1} \cdot f $$
$$\exists C_{2} > 0, \exists N_{2} \in \mathbb{N},\ \forall n > N_{2},\ \varphi_{2} \leqslant C_{2} \cdot g $$
From above $\varphi = \varphi_{1} \cdot \varphi_{2} \leqslant C_{1} \cdot f \cdot C_{2} \cdot g = C_{1} \cdot C_{2} \cdot f \cdot g $ when $ n>N=max(N_{1},N_{2}) $.
Accordingly, we can also see that there is a second general property:
$$O(f)+O(g) = O(f+ g )$$
The proof uses the same technique.
Definitions:
$$O(f)\cdot O(g) = \left\lbrace a\cdot b \colon (a,b)\in O(f)\times O(g) \right\rbrace $$
$$O(f)+O(g) = \left\lbrace a + b \colon (a,b)\in O(f)\times O(g) \right\rbrace $$